Autogenic Relaxation with Audiomusic Instrumental Media on Pain Scale in Post Sectio Caesarea Patients - Ningsih Ismi, Dian Ayu; Aprina, Aprina; Purwati, Purwati (Poltekkes Kemenkes Tanjung Karang, 2024)
Pain on the first day of cesarean section creates psychological anxiety and fear of pain after the drug reaction ends. One method of pain management is autogenic relaxation therapy using instrumental audiomusic media. This study aims to determine the effect of autogenic relaxation using instrumental audio music on the pain scale in post-cesarean section patients at RSUD Dr. H. Abdul Moeloek Lampung Province. This research uses a quantitative approach with a pre-experimental one-group pretest-posttest design. The research was conducted from February to March 2023. The population in this study consisted of patients after the cesarean section. The sampling method in this research used the Accidental Sampling technique and obtained a sample of 32 respondents. The instrument used to measure the pain scale is the Numerical Rating Scale (NRS), an observation sheet that records the pain scale before and after the procedure. Statistical tests use the Wilcoxon signed rank test. The research results showed that the average pain scale decreased from 7.28 to 6.21 before and after the intervention. Thus, a p-value of 0.000 was obtained (p-value<0.05), which means that there was an effect of autogenic relaxation using instrumental audio music on the pain scale in post-cesarean section patients at RSUD Dr. H. Abdul Moeloek, Lampung Province in 2023. Researchers suggest that nurses or midwives treat pain not only with pharmacological therapy but also with non-pharmacological therapy, namely autogenic relaxation with instrumental audio-music media.